A Fiqh Muamalah Analysis Of Merchant Discount Rate (MDR) In Qris Transactions and Its Implications For Economic Justice - Sayyid Muttaqin (International Journal of Management and Business Economics, 2026)
The implementation of the Quick Response Code Indonesian Standard (QRIS) has accelerated digital payment transformation, particularly among micro, small, and medium enterprises (MSMEs). However, the application of the Merchant Discount Rate (MDR) in QRIS transactions has raised debates regarding justice, transparency, and public welfare in Islamic economics. This study aims to analyze MDR implementation in QRIS transactions from the perspective of fiqh muamalah. The novelty of this research lies in examining MDR not merely as a transaction fee but also as a contemporary muamalah practice assessed through the principles of ujrah, al-‘adl, maslahah, tarāḍī, and the avoidance of gharar and ẓulm. This study employs a qualitative method with a normative-empirical approach through literature review and regulatory analysis. The findings indicate that MDR is permissible (mubāḥ) if implemented transparently, fairly, proportionally, and based on mutual consent. Nevertheless, limited transparency and merchant understanding may create economic injustice. Therefore, transparent regulation and financial literacy are essential to protect MSME welfare and achieve maqāṣid al-sharī‘ah.